What can Gaia proper motions tell us about Milky Way dwarf galaxies?. Issue 67 (17th July 2015) - Jin, S.; Helmi, A.; Breddels, M.
Abstract : We present a proper-motion study on models of the dwarf spheroidal galaxy Sculptor, based on the predicted proper-motion accuracy of Gaia measurements. Gaia will measure proper motions of several hundreds of stars for a Sculptor-like system. Even with an uncertainty on the proper motion of order 1.5 times the size of an individual proper-motion value of ∼10 mas/century, we find that it is possible to recover Sculptor's systemic proper motion at its distance of 79 kpc.